Why Icebergs Float Exploring Science in Everyday Life - Morris, Andrew (UCL Press, 2016)
From paintings and food to illness and icebergs, science is happening everywhere. Rather than follow the path of a syllabus or textbook, Andrew Morris takes examples from the science we see every day and uses them as entry points to explain a number of fundamental scientific concepts - from understanding colour to the nature of hormones - in ways that anyone can grasp. While each chapter offers a separate story, they are linked together by their fascinating relevance to our daily lives.